Recent trends in the Croatian agricultural business sector - Juračak, Josip; Vukalović, Dario (Applied Studies in Agribusiness and Commerce, 2013)
The purpose of this paper is to explore recent trends in the Croatian agriculture and forestry business sector and compare it with the Croatian economy as a whole. This topic is considered interesting because recent business years have been heavily influenced by the global financial crisis. Many authors would say that agriculture, as a specific branch of the economy, does not follow general trends, but is affected rather by other factors, especially such as environmental ones. The global financial crisis had the most negative impact on the Croatian economy in the 2008/2009 period, when the GDP growth rate tumbled from 2.4% to -5.8%. Although some positive movements have been recorded since 2009, a recession is still going on. Based on information from the National Financial Agency (FINA) database we found that during the period 2007-2011, agricultural firms experienced the same trends as the whole economy, except in terms of average monthly salaries and employment. However, due to the impact of / on? agricultural products prices and yields, in two year period from 2008 to 2010, agricultural firms recorded an almost linear fall in revenues, while the national business sector on the whole experienced a sharp fall in revenues in 2009 and then only a modest fall in 2010.